Impaired Health-related Quality of Life and Related Risk Factors among U.S. Adults with Asthma - Pate, Cynthia A. (J Asthma, 2018)
OBJECTIVE: This study assessed Health-related Quality of Life (HRQoL) and related risk factors among adults with asthma in the United States. Using the 2015 Behavioral Risk Factor Surveillance System (BRFSS), we examined the association between four domains of impaired HRQoL and selected explanatory factors. METHODS: A BRFSS sample of 39 321 adults with asthma was used in this study. We examined the association between fair/poor health, ≥14 mentally unhealthy days, ≥14 physically unhealthy days, and ≥14 days of activity limitation and selected explanatory variables (sex, race/ethnicity, age, annual household income, healthcare coverage, physical activity, smoking status, Body Mass Index (BMI), having a coexisting disease, and being diagnosed with depression) using multivariable logistic regression models. RESULTS: Income, physical activity status, smoking status, coexisting diseases, and depression were strongly associated with all HRQoL domains. Blacks had significantly less ≥14 physically unhealthy days (23.4%; aPR = 0.82 [95% CI: 0.72, 0.92]) and ≥14 days of activity limitation (18.3%; aPR = 0.81 [0.70, 0.94]) and Hispanics had significantly more fair/poor health (38.4%; aPR= 1.31 [1.18, 1.45]) than whites. Underweight and obese had significantly more fair/poor health, and underweight significantly more ≥14 physically unhealthy days, compared with normal weight. Adults aged 55 years or older had significantly less ≥14 mentally unhealthy days than adults 18–24 years. CONCLUSIONS: Multiple factors were associated with impaired HRQoL. Providing strategies to address potential risk factors such as low income, physically inactive, smoker, and obese or underweight should be considered to improve HRQoL among adults with asthma.